From stress to screen: relationship between negative life events and short video addiction among college students: a chain-mediated effect of depression and experiential avoidance - Liu, Yan; Zhan, Yangyang; Liu, Yaorong (Frontiers in Psychology, 2025)
IntroductionIn contemporary society, short video addiction has become an increasingly prevalent behavioral disorder among young individuals, raising concerns about its underlying causes and development.MethodA survey was conducted on a sample of Chinese college students (N = 843) to explore the impact of negative life events on short video addiction, as well as the underlying mechanisms.Results(1) Negative life events exert a significant positive influence on short video addiction among young people; (2) both depression and experiential avoidance serve as mediators in the relationship between negative life events and short video addiction; and (3) beyond their independent mediating effects, depression and experiential avoidance collectively function as a chained mediating mechanism in this process.DiscussionBy elucidating the dynamic interplay between external environmental stressors and internal psychological processes, this research contributes to the theoretical under-standing of short video addiction among college students. Furthermore, it provides a valuable foundation for the development of targeted intervention strategies and mental health support programs aimed at mitigating the adverse effects of negative life events on digital behavior.